KAJIAN IMPLEMENTASI NORMA, STANDAR, PROSEDUR DAN KRITERIA DALAM PENGORGANISASIAN KAWASAN KESATUAN PENGELOLAAN HUTAN - Sylviani Sylviani; Elvida Yosefi Suryandari (Jurnal Analisis Kebijakan Kehutanan, 2013)
Forest Management Unit (FMU) is an area of forest land in site level that managed to meet sustainable forest management in along term plan. One or more forest functions (conservation, protection and production) can be included in an FMU, but the FMU will be classified by its dominant forest function. KPH has been established in several provinces, but a few them has not yet operational. Institutional aspects such as policy and organization are having problem in the implementation of FMU. The objective of the study are : (1) to analyze the implementation of norms, standards, procedures and criteria (NSPC) of FMU and (2 )to analyze the organization's policies in the management of FMU.The study was held at the Dampelas Tinombo FMU in Central Sulawesi; Way Terusan FMU, and Batu Tegi FMU in Lampung Province. In polic analysis used a retrospective method model, while in organizational structure analysis used qualitative descriptive method. The results showed that the policy about FMU NSPC has been implemented by each FMU in research location. It can be seen from the master plan of "forest management planning and forest governance". This study examines the FMU organization through the current organizational structure. There are similarities in the organizational structure of FMU indicated through the division of labor, authority, span of control and division of the department. However, there are differences in the classification of departmentalizing types. The differences are caused by differences in local conditions, aswell as the potential for each policy in research location. Form of organizational FMU at the site study has a characteristics "functional organizational structure". The positives of this organization type will continue to adapt to their environment in order to keep growing to wards the vision and mission that have been made. If there is a policy changes, organizations need to change the internal of organization, for example by adjusting its organizational structure. Form of FMU Organizational as Regional Technical Implementation Unit, FMU can accommodate the interests of the goverment through departmentalizing based on NSPC criteria approach. Coordination among stakeholders through funding has done, either by the central or local governments. For better management of the FMU it is recommended : (1) Derivatives policy is required on the tasks and role of FMU in detail, to fasilitate implementation and management, and (2) Prefaring the conditions of FMU organizations to make adaptation if there is a policy change related to FMU organization. Interms of funding, the central government should al locate funds through related technical unit until FMU can operate independent lyand the rules about capabilities and mobilization of human resources are needed.